Design and numerical study on bionic columns with grooves under lateral impact. (March 2020) - Song, Jiafeng; Xu, Shucai; Liu, Shengfu; Huang, Han; Zou, Meng
Abstract: Thin-walled structures are widely used as strengthened parts or energy absorbers in vehicle bodies. Thus, the collapse behaviors and mechanical properties of thin-walled columns under static and dynamic loadings have drawn much attention. During vehicle side crash accidents, the contact parts of vehicles usually deform in the bending collapse mode. Thus, it is significantly important to investigate the collapse behaviors of these parts under the lateral impact. In this study, a new type of Bionic Column with Groove (BCG) was designed, with the inspiration from the lodging resistance features and lightweight of cornstalks. To understand the crashworthiness of BCGs under the lateral impact, we first experimentally established and validated the finite element models of BCGs and Circular Column (CC) under the lateral loading. The simulations agreed well with the experimental tests. Then, the crashworthiness of CC and the BCG were compared, and BCG2-90 outperformed normal CC in specific energy absorption (SEA), bending strength (BS)and crushing force efficiency (CFE). Parametric analyses showed the parameters of the bionic groove significantly affected the crashworthiness of BCG2-90. Finally, a response surface method showed the SEA, BS, and CFE of the optimal design increased by 93.10%, 50.96%, and 15.05% compared with CC respectively. Moreover, the mass reduction relative to CC was 2%. The results from the optimization demonstrate BCG is superior over CC in overall crashing behavior under the lateral impact. Highlights: A new bionic column was designed inspired by the structure of cornstalk. The lateral loading simulation of bionic column was verified by experiment. The parameters of bionic groove had effect on the energy absorption of column. The bionic structures were optimized by response surface optimization method.